What is the evidence for the impacts of airborne anthropogenic noise on wildlife? A systematic map update - Léa Terray; Benjamin Petiteau; Guillaume Dutilleux; Sylvie Vanpeene; Pamela Amiard; Romain Sordello; Yorick Reyjol (Environmental Evidence)
Abstract Background Noise from human activities is a major concern for wildlife, with numerous studies demonstrating significant impacts. In 2020, Sordello and collaborators systematically mapped the literature on the impacts of anthropogenic noise on wildlife up to 2018. Since then, research on this topic has continued to grow steadily. To reflect these developments, we present an updated systematic map encompassing studies published through 2023, exclusively focused on airborne noise. Methods The method follows the a priori protocol published by Sordello and collaborators in 2019. The present work includes literature searches by Sordello et al. (2020) and a complementary search update performed on 2020–2023. Literature from Sordello et al. (2020) was re-screened to align with the updated scope, now restricted to airborne noise. For the update, both peer-reviewed and grey literature were retrieved from Scopus, the Web of Science Core Collection, and Google Scholar. Titles, abstracts, and full texts were screened by eligibility criteria, and included articles were coded. We included all wild terrestrial or semi-aquatic taxonomic groups, and anthropogenic noise from various sources (e.g., transport, urban, recreational) was considered, along with all relevant outcomes (e.g., behaviour, reproduction, physiology). Review findings Sordello et al. (2020) provided 1,794 articles, of which 466 were retained after re-screening the full texts. The search update yielded 13,698 citations, resulting in 397 relevant articles. A total of 863 articles were included in the map (665 primary research studies, 196 reviews and meta-analyses, 2 modelling papers). Most studies have been conducted in the USA. Birds are the most studied taxonomic group (64%), followed by mammals (22%); transportation is the most studied source of noise (43%), followed by urban noise (24%); behaviour (27%) and vocal communication (25%) are the most studied outcomes. Conclusion The map represents an updated state of the art on the impact of airborne anthropogenic noise on wildlife and can serve as a starting point for further syntheses of evidence. Three clusters of knowledge were identified as suitable candidates for future syntheses: (1) What is the impact of anthropogenic noise on mammals’ behaviour? (2) What is the impact of anthropogenic noise on birds’ reproductive success? (3) What is the impact of anthropogenic noise on species richness and diversity? In addition, the knowledge gaps identified may be used to inform future research and address the apparent imbalance in the published research: many taxonomic groups are still understudied (e.g., especially reptiles and arachnids), many potential sources of noise disturbance are neglected (e.g., recreational and military noise) and the impacts of noise are unevenly studied between taxonomic groups.